Introduction of In Vivo Confocal Laser Endomicroscopy and Real-Time Telepathology for Remote Intraoperative Neurosurgery-Pathology Consultation. Issue 3 (9th September 2022) - Park, Marian T.; Abramov, Irakliy; Gooldy, Timothy C.; Smith, Kris A.; Porter, Randall W.; Little, Andrew S.; Lawton, Michael T.; Eschbacher, Jennifer M.; Preul, Mark C.
Abstract : BACKGROUND: Precise communication between neurosurgeons and pathologists is crucial for optimizing patient care, especially for intraoperative diagnoses. Confocal laser endomicroscopy (CLE) combined with a telepathology software platform (TSP) provides a novel venue for neurosurgeons and pathologists to review CLE images and converse intraoperatively in real-time. OBJECTIVE: To describe the feasibility of integrating CLE and a TSP in the surgical workflow for real-time review of in vivo digital fluorescence tissue imaging in 3 patients with intracranial tumors. METHODS: Although the neurosurgeon used the CLE probe to generate fluorescence images of histoarchitecture within the operative field that were displayed on monitors in the operating room, the pathologist simultaneously remotely viewed the CLE images. The neurosurgeon and pathologist discussed in real-time the histological structures of intraoperative imaging locations. RESULTS: The neurosurgeon placed the CLE probe at various locations on and around the tumor, in the surgical resection bed, and on surrounding brain tissue with communication through the TSP. The neurosurgeon oriented the pathologist to the location of the CLE, and the pathologist and neurosurgeon discussed the CLE images in real-time. The TSP and CLE were integrated successfully and rapidly in the operating room in all 3 cases. No patient had perioperative complications. CONCLUSION: Two novel digital neurosurgical cellular imaging technologies were combined with intraoperative neurosurgeon-pathologist communication to guide the identification of abnormal histoarchitectural tissue features in real-time. CLE with the TSP may allow rapid decision-making during tumor resection that may hold significant advantages over the frozen section process and surgical workflow in general.